Cambridge global English learner$1 (Bs book 4 /s - Boylan, Jane; Medwell, Claire (New York : Cambridge, 2015)
Cambridge Global English (1-6) is a six-level Primary course following the Cambridge Primary English as a Second Language Curriculum Framework developed by Cambridge English Language Assessment. Learner's Book 4 provides core input for Stage 4 with nine thematic units of study and five review spreads. Units end with an engaging project and opportunity for self-assessment. Richly illustrated units contain six lessons, each developed around a unifying theme. The materials feature skills-building tasks for listening, reading, writing and speaking. 'Language detective' features focus on language awareness, and 'Tips' boxes on key tips for specific skills. Texts have variety: factual and fictional, dialogue and poetry covering a range of topics. Accompanying Audio CDs (2) include listening material for Stage 4 Learner's and Activity Books. CEFR Level: towards A2.
Keywords: Learner's book